2013
DOI: 10.1007/s13762-013-0346-5
|View full text |Cite
|
Sign up to set email alerts
|

Metal ion remediation by polyamidoamine dendrimers: a comparison of metal ion, oxidation state, and titania immobilization

Abstract: The exceptional ability of dendrimers to coordinate metal ions yields the potential for many applications including wastewater remediation, which is the focus of this study. Here, the comparison of metal ion removal rate from simulated wastewater by generation 4 dendrimers with external hydroxyl functional groups (G4-OH) is evaluated for Ni 2? , Fe 2? , and Fe 3? ions. Ni 2? to amine complexation occurred more rapidly than Fe 3? , which was more rapid than Fe 2? complexation. These results indicate that both c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In this context, there are few reports that have studied the effect of oxidation number of heavy metals in the adsorption process and particularly, the works related with the adsorption by complexation mechanism have considered this property. For example, in the removal of Ni 2+ , Fe 2+ and Fe 3+ (with external hydroxyl functional groups) was demonstrated that high-valence species complex more quickly than the lowvalence due to the ability to accept more of the ligand's electron donation, where the adsorption followed the trend Ni 2+ > Fe 3+ > Fe 2+ [70].…”
Section: Adsorbate Properties and Adsorption Conditionsmentioning
confidence: 99%
“…In this context, there are few reports that have studied the effect of oxidation number of heavy metals in the adsorption process and particularly, the works related with the adsorption by complexation mechanism have considered this property. For example, in the removal of Ni 2+ , Fe 2+ and Fe 3+ (with external hydroxyl functional groups) was demonstrated that high-valence species complex more quickly than the lowvalence due to the ability to accept more of the ligand's electron donation, where the adsorption followed the trend Ni 2+ > Fe 3+ > Fe 2+ [70].…”
Section: Adsorbate Properties and Adsorption Conditionsmentioning
confidence: 99%
“…Figure 2 suggests the removal mechanism of positive metal ions through dendrimers-Ti composite. Castillo et al [14] studied the removal capacity of Ni and Fe oxidation states utilizin 4th generation PAMAM with the G4-OH group. They also investigated the influence o G4-OH immobilization on Ti enhanced materials and their chelating potential on Ni(I removal.…”
Section: Titanium Supported Dendrimersmentioning
confidence: 99%
“…Metals can become mobilized, leading to soil and groundwater contamination that increase the possibility of entering into the food chain and finally into the human body (Taghipour et al 2013;Shaheen et al 2014a, b, c). Thus, remediation of PTMs in contaminated soils has received increasing attention and is an important issue for adequate environmental management (Ok et al 2011a;Castillo et al 2014;Shaheen et al 2015).…”
Section: Introductionmentioning
confidence: 99%